Salient aspects of self-treatment in substance abusers - Bayraktar, Ayşe Hande; Aktürk, İlker and Yaman, Ömer Miraç (Journal of Dependence, 2024)
Objective: Addiction, which starts with substance use, is a process formed by the combination of many factors. Addiction, which is a biopsychosocial problem, is characterised by recovery and relapses. Since addiction is not a onedimensional problem, the treatment process should not be considered one-dimensional. Therefore, addiction treatment should be handled with a holistic approach. At this point, addiction treatment should be continuous and continue for many years. For this reason, the treatments applied should be complicated and aimed at harm reduction. The aim of the research is to examine the prominent factors in the self-treatment method in substance users. Method: In this study, the phenomenological research method included in qualitative research was used. A semistructured interview form was used in the interviews with 16 participants. The data obtained were interpreted according to the descriptive analysis method. Results: Within the scope of the data, 3 themes were created. These themes are Methods Used in Self-Healing Process, Motivation Source of Addicts in Self-Healing, and Compulsory Self-Treatment due to Lack of Substance. Conclusion: The prominent elements in terms of self-treatment strategies; drug use, environmental change, doing activities while coping with substance cravings, inability to obtain the substance, spiritual orientation, taking responsibility and family support. These findings may contribute to the development of more effective support and intervention programs for the self-treatment processes of individuals with substance use disorders.